2016
DOI: 10.1111/1744-9987.12437
|View full text |Cite
|
Sign up to set email alerts
|

Ankle‐Brachial Index and Long‐Term (10 Years) Survival of Nondiabetic Hemodialysis Patients

Abstract: Low (<0.9) and high (>1.4) ankle brachial index (ABI) is associated with a higher cardiovascular (CV) mortality in the general and hemodialysis (HD) population. The aim of our study was to determine the impact of ABI on long-term survival of 52 non-diabetic HD patients. The ABI was determined using an automated, non-invasive waveform analysis device. Patients were divided into three groups: low (<0.9), normal (0.9-1.4) and high (>1.4) ABI. Patients were observed from the date of ABI measurement until their dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…In our study, the majority of the patients presented vascular stiffness according to ABI, probably due to the severity of SHPT and high prevalence of hyperphosphatemia. Despite several studies in which an ABI>1.3 demonstrated a higher occurrence of cardiovascular events, in patients either on dialysis 10,[12][13][14] or not [28][29][30][31][32] , we did not find studies in patients with severe SHPT. London et al 33 demonstrated that low bone turnover was related to peripheral arterial disease (PAD) and it was inversely related to parathyroidectomy (PTX).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In our study, the majority of the patients presented vascular stiffness according to ABI, probably due to the severity of SHPT and high prevalence of hyperphosphatemia. Despite several studies in which an ABI>1.3 demonstrated a higher occurrence of cardiovascular events, in patients either on dialysis 10,[12][13][14] or not [28][29][30][31][32] , we did not find studies in patients with severe SHPT. London et al 33 demonstrated that low bone turnover was related to peripheral arterial disease (PAD) and it was inversely related to parathyroidectomy (PTX).…”
Section: Discussioncontrasting
confidence: 90%
“…Obstructive arterial disease can be identified by low ABI (<0.9), and high ABI (>1.3) has been associated with vascular calcification due to arterial incompressibility 10,11 . In dialysis patients, low and high ABI were related to cardiovascular events and mortality 10,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ABI measurement alone does not reliably identify patients with media calcification. Previously, both a low and high ABI were found to be independently associated with all-cause and cardiovascular mortality in hemodialysis patients (7,9,29). A low ABI has also been shown to predict mortality in PD patients (1,30).…”
Section: Discussionmentioning
confidence: 99%
“…Similar association was found between renal function, cardiovascular events and high ABI[ 94 ]. In a study on 52 hemodialysis patients by Bevc et al [ 95 ], survival analysis showed higher risk for cardiovascular death in patients with ABI > 1.4. It appears that the systemic nature of atherosclerosis is only partly responsible for these effects of changed ABI and that increased arterial stiffness and consequent hemodynamic changes play an integral role as well[ 96 ].…”
Section: Ankle-brachial Indexmentioning
confidence: 99%